2022
DOI: 10.1007/s00392-022-02053-8
|View full text |Cite
|
Sign up to set email alerts
|

Guideline-directed medical therapy is similarly effective in heart failure with mildly reduced ejection fraction

Abstract: Aims Current guidelines recommend that disease-modifying pharmacological therapies may be considered for patients who have heart failure with mildly reduced ejection fraction (HFmrEF). We aimed to describe the characteristics, outcomes, provision of pharmacological therapies and dose-related associations with mortality risk in HFmrEF. Methods and results We explored data from two prospective observational studies, which permitted the examination of the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
2
7
0
2
Order By: Relevance
“…While LVEF improved significantly in both treatment groups, these improvements were more pronounced for individuals that were subject to ARNI treatment as compared to ACEI treatment. Several prior studies have reported similar LVEF improvement in patients diagnosed with HFrEF [17][18][19][20]. The PARAGON-HF study determined that sacubitrilvalsartan treatment was associated with more pronounced absolute and relative benefit as compared to valsartan in HFpEF patients when this therapeutic regimen was initiated during the high-risk window following hospitalization, in line with the present study [21].…”
Section: Discussionsupporting
confidence: 88%
“…While LVEF improved significantly in both treatment groups, these improvements were more pronounced for individuals that were subject to ARNI treatment as compared to ACEI treatment. Several prior studies have reported similar LVEF improvement in patients diagnosed with HFrEF [17][18][19][20]. The PARAGON-HF study determined that sacubitrilvalsartan treatment was associated with more pronounced absolute and relative benefit as compared to valsartan in HFpEF patients when this therapeutic regimen was initiated during the high-risk window following hospitalization, in line with the present study [21].…”
Section: Discussionsupporting
confidence: 88%
“…The clinical characteristics and outcomes in HFmrEF population were found in a large part to be intermediate between heart failure with reduced ejection fraction (HFrEF) and heart failure with preserved ejection fraction (HFpEF). 1 These findings were consistent with a previous analysis from European Society of Cardiology (ESC) heart failure longterm registry 2 as well as a prospective international multiethnic cohort study. 3 However, whether HFmrEF is a distinct entity from HFrEF and HFpEF remains a heated debate.…”
supporting
confidence: 91%
“…The prospective evaluation of the diagnostic efficacy of the 2010 United Kingdom National Institute for Clinical Excellence guidelines on Chronic Heart Failure (NICE-CHF) is an observational cohort study including people newly referred to secondary care for suspected heart failure. 9 Consecutive unselected patients from a primary care catchment of over 750,000 people between May 2012 and May 2013, who had signs and/or symptoms of chronic heart failure as well as elevated natriuretic peptides (N-terminal pro B-type natriuretic peptide [NT-proBNP] ≥125pg/L), were included.…”
Section: Methodsmentioning
confidence: 99%